مساءلة الموتى وإحياء ذاكرة المنفى قراءة في "رواية شبح الكليدوني" لمحمد مفلاح. (مجلة إحالات, 2025)
يشكل الفعل الإنساني في النص السّردي المعاصر محورا فاعلاً يتأسس عليه النص ويكوّن نواة تنطلق منها أو ترتدُّ إليها موضوعات لا متناهية ذات صلة بالتجربة الذاتية أو الحس الإنساني. فالفعل الإنساني الذي يعمل على إحياء كالكتابة الموسومة بــــ: مساءلة الموتى، وإحياء ذاكرة المنفى" (ما بعد الموت) يبدو في بنية العمل السّردي المنجز بالدرجة الأولى تجربة شخصية تنبع من حاجة نفسية هي التي توجهه، والخطاب السّردي بدوره لا يخرج عن هذه القاعدة، إذ هو جواب عن سؤال أو تلبية لرغبة، أو إحياء لسياق ثقافي معين قد يعتري الذات المبدعة، فليس هناك سرد بدون غرض وهدف محدد يوجهه وذلك داخل تفاعل المبدع مع سياقه الثقافي حيث يتداخل في الكتابة كل من الماضي والحاضر(شبح الكليدوني)، فهي واقعة ملتبسة لا تخلو من ثنائية خطابية قائمة على صراع يتولد عبر مواجهة الكاتب لمجتمعه. The human act in contemporary narrative text is an active focus on which the text is based and which is a nucleus from which innumerable themes or themes are related to self-experience or human sense. The human act that enlists the type of writing that is characterized by the accountability of the dead and the revival of the memory of exile (post-mortem) appears in the structure of narrative work performed primarily as a personal experience stemming from a psychological need that guides it. The narrative discourse in turn does not depart from this rule. It is an answer to a question or a response to a desire, or to the revival of a certain cultural context that may be the creative self. There is no narration without a specific purpose and purpose directed at it within the creative interaction with its cultural context, where the past and the present are intertwined. Without a rhetorical dualism based on conflict generated by confrontation Writer for society.